The role of panglima laot towards fisheries management based on ecosystem approach in Banda Aceh City. Issue 1 (February 2021) - Rahmah, A; Salmarika, S; Miswar, E
Abstract: Panglima Laot was indigenous institutions of Aceh that hand to realize sustainable fisheries management particularly with an ecosystem approach. The objective of this study is to evaluated status of Panglima Laot on fisheries management based on ecosystem approach. This research was conducted in 2017 in Banda Aceh City. Data analysis used Composite index with multy criteria analysis and then visualized by flag modelling. The result of this study showed Panglima Laot status was 'good' category. Composite value of Lhok Pasie Tibang Panglima Laot is 66, 6, Lhok Kuala Aceh Panglima Laot 62, 5 and Lhok Kuala Cangkoi Panglima Laot 72, 6.